Relationship between newborn mid-upper-arm circumference and birth weight - Muhammad Anwar Taufiq; Djauriah A. Madjid; J. S. Lisal; Dasril Daud (Indonesian Pediatric Society Publishing House, 2009)
Background  Recording  an  accurate  birth  weight  by  primary health care workers has been a problem in rural areas, leading to a search  for  an alternative, inexpensive, age independent and noninvasive method to predict neonatal well being. Mid-upper-arm circumference (MUAC) might be  an  alternative anthropometric measurement useful  to  estimate the state of nutrition. Objective  To  evaluate  the  relationship  between  MUAC  and birth weight  in  low birth weight (LBW) and normal birth weight (NBW) infants. Methods  We  measured birth weight and  MUAC  of  newborn babies  of  various gestational ages  at  Siti Fatimah Maternity  and Children's Hospital  and  Dr.  Wahidin Sudirohusodo  General Hospital, Makassar,  South  Sulawesi, Indonesia.  Correlation tests and diagnostic accuracy using different cut-off points were performed Results There were 892 live birth newborns (117 LBW and  775 NBW) included in the study.  The  sensitivity, specificity, positive predictive value, and negative value  for  MUACs  of<  10.3  em  were 94.9  %,  99.9%, 99.1%, and 99.2%, respectively.  The  sensitivity, specificity, positive predictive value, and negative value  for  MUAC < 10.4  em  were 99.1  %,  99.6%, 97.5%, and 99.9%, respectively. The  sensitivity, specificity, positive predictive value, and negative value for MUAC < 10.5  em  were 100%,99.4%, 95.9%, and 100%, respectively. Conclusion  There  is  a strong correlation between  MUAC  and birth weight. Birth weight can be predicted with the following equation: Birth weight= -1776.383  +  (416.95 newborn  MUAC value).  The  optimal cut-off point  for  the newborn MUAC value  for LBW infants  is<  10.5 em.